Tobacco Use Assessment and Treatment in Cancer Patients: A Scoping Review of Oncology Care Clinician Adherence to Clinical Practice Guidelines in the U.S. (16th November 2018) - Price, Sarah N.; Studts, Jamie L.; Hamann, Heidi A.
Abstract: Background: Smoking after a cancer diagnosis negatively impacts health outcomes; smoking cessation improves symptoms, side effects, and overall prognosis. The Public Health Service and major oncology organizations have established guidelines for tobacco use treatment among cancer patients, including clinician assessment of tobacco use at each visit. Oncology care clinicians (OCCs) play important roles in this process (noted as the 5As: Asking about tobacco use, Advising users to quit, Assessing willingness to quit, Assisting in quit attempts, and Arranging follow‐up contact). However, OCCs may not be using the "teachable moments" related to cancer diagnosis, treatment, and survivorship to provide cessation interventions. Materials and Methods: In this scoping literature review of articles from 2006 to 2017, we discuss (1) frequency and quality of OCCs' tobacco use assessments with cancer patients and survivors; (2) barriers to providing tobacco treatment for cancer patients; and (3) the efficacy and future of provider‐level interventions to facilitate adherence to tobacco treatment guidelines. Results: OCCs are not adequately addressing smoking cessation with their patients. The reviewed studies indicate that although >75% assess tobacco use during an intake visit and >60% typically advise patients to quit, a substantially lower percentage recommend or arrange smoking cessation treatment or follow‐up after a quit attempt. Less than 30% of OCCs report adequate training in cessation interventions. Conclusion: Intervention trials focused on provider‐ and system‐level change are needed to promote integration of evidence‐based tobacco treatment into the oncology setting. Attention should be given to the barriers faced by OCCs when targeting interventions for the oncologic context. Implications for Practice: This article reviews the existing literature on the gap between best and current practices for tobacco use assessment and treatment in the oncologic context. It also identifies clinician‐ and system‐level barriers that should be addressed in order to lessen this gap and provides suggestions that could be applied across different oncology practice settings to connect patients with tobacco use treatments that may improve overall survival and quality of life. Abstract : Despite the availability of evidence‐based cessation approaches and guidelines, smoking rates remain high among individuals diagnosed with cancer. In this article, the past 10 years of research addressing barriers to providing tobacco cessation treatment is reviewed, with a focus on increasing adherence to standard tobacco treatment practices among oncology care providers.